Examining the use and effectiveness of Elder Abuse Protocols: a Western Australian case study - Blundell, Barbara; Timms, Diedre (2018)
Elder abuse protocols have been developed for use in different jurisdictions over a number of years to guide staff and professionals in responding to elder abuse. There usage and effectiveness has been unclear, as they have generally not been evaluated. This project focussed on exploring the usefulness and effectiveness of the Elder Abuse Protocols developed by Alliance for the Prevention of Elder Abuse: Western Australia in 2013, as well as developing an updated version of the Protocol and supporting the new protocol with a number of workshops for stakeholders. Three focus groups and an online survey were conducted with stakeholder organisations and people working with older people in order to examine the usefulness and effectiveness of the Protocols. The research data, along with a review of literature and similar documents from other jurisdictions, informed an updated version of the Protocol.